Tailoring education of adults with cognitive impairment in the inpatient hospital setting: A scoping review. (8th October 2020) - D'Cruz, Kate; Meikle, Louise; White, Megan; Herrmann, Alicia; McCallum, Carrie; Romero, Lorena
Abstract: Introduction: Education seeks to empower clients to attain and maintain knowledge and skills, and in the context of occupational therapy, to enable occupational participation. While education is routinely provided in the inpatient hospital setting, little is known about how education is best adapted to meet the needs of clients with cognitive impairment. The purpose of this scoping review was to determine what is currently known about approaches to educating adults with cognitive impairment in the inpatient hospital setting. Methods: Five databases were systematically searched to find studies that reported on the use of education in the inpatient hospital setting with adults with cognitive impairment. Results: Ten articles were retrieved from the search with duplication of authors across the articles, indicating a small group of research and researchers. Cognitive impairment was not well assessed across all the studies and none included participants with severe cognitive impairment. A number of barriers to education were identified, including time constraints, uncertainty around who should be providing education, a shortage of resources, and client‐related barriers such as cognitive deficits. From the retrieved studies it was found that education should occur at multiple time points, be individually tailored, and utilise mixed modal approaches such as verbal and written methods. There was also a preference for less use of jargon, and engagement with carers and clients where possible. Conclusion: This scoping review highlights factors impacting the provision of education tailored to the needs of clients with cognitive impairment in the inpatient setting. The findings also call to attention the need for better assessment of cognition to guide provision of tailored education, as well as future studies exploring how to best educate clients with not only mild/moderate cognitive impairment but also more severe impairments.